PERAN ORANGTUA SINGLE PARENT LAKI-LAKI DALAM KELUARGA DI DESA BUKIT PAYUNG KECAMATAN BANGKINANG KABUPATEN KAMPAR - Isti Fi Utami; Swis Tantoro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Family is the smallest unit in the community, which consists of a house consisting of father, mother and child. There are no associated families like Single Parent who only live with their children without a mother in the family. So that all roles of mother in the father family are taken over, such as child care, child rearing, earning a living to take care of household matters. In the Extended family, this is certainly very helpful for male Single Parent in the family, although not all Single Parent receive support from close relatives. This study aims to find out how the dual role of male batteries for Single Parents and the role of Extended families in the family in the village Bukit Payung. This research uses role theory and with descriptive qualitative methods. The Informants in this study were eight people with observations and in-depth data acquisition techniques. The results of this study are that male Single Parent are not careful when caring for children. When raising children, Single Parent advise more because the age of the child is between 5-17 years. In taking care of household affairs is not difficult for Single Parent male parents, because everything is very simple like cooking rice with a rice cooker or washing with a washing machine. Bukit Payung Village is a transmigration village, so the work of Single Parents as palm and rubber growers working in their own garden or in another is average. The role of the Extended Family is certainly very helpful for Single male Parents in the family, especially for those who have young children, although the family role here only looks after children, but it helps when the parent are busy to work.  Key word: Role, Family, Single Parent, Extended Family